Development of an MRI biomarker sensitive to tetrameric visual arrestin 1 and its reduction via light‐evoked translocation in vivo. Issue 2 (28th October 2014) - Berkowitz, Bruce A.; Gorgis, Jawan; Patel, Ankit; Baameur, Faiza; Gurevich, Vsevolod V.; Craft, Cheryl M.; Kefalov, Vladimir J.; Roberts, Robin
ABSTRACT: Rod tetrameric arrestin 1 (tet‐ARR1), stored in the outer nuclear layer/inner segments in the dark, modulates photoreceptor synaptic activity; light exposure stimulates a reduction via translocation to the outer segments for terminating G‐protein coupled photo‐transduction signaling. Here, we test the hypothesis that intraretinal spin‐lattice relaxation rate in the rotating frame (1/T1ρ), an endogenous MRI contrast mechanism, has high potential for evaluating rod tet‐ARR1 and its reduction via translocation. Dark‐ and light‐exposed mice (null for the ARR1 gene, overexpressing ARR1, diabetic, or wild type with or without treatment with Mn 2+, a calcium channel probe) were studied using 1/T1ρ MRI. Immunohistochemistry and single‐cell recordings of the retinas were also performed. In wild‐type mice with or without treatment with Mn 2+, 1/T1ρ of avascular outer retina (64% to 72% depth) was significantly ( P < 0.05) greater in the dark than in the light; a significant ( P < 0.05) but opposite pattern was noted in the inner retina (<50% depth). Light‐evoked outer retina Δ1/T1ρ was absent in ARR1 ‐null mice and supernormal in overexpressing mice. In diabetic mice, the outer retinal Δ1/T1ρ pattern suggested normal dark‐to‐light tet‐ARR1 translocation and chromophore content, conclusions confirmed ex vivo . Light‐stimulated Δ1/T1ρ in inner retina was linked to changes in blood volume. Our data support 1/T1ρ MRI for noninvasively assessing rod tet‐ARR1 and its reduction via protein translocation, which can be combined with other metrics of retinal function in vivo .—Berkowitz, B. A., Gorgis, J., Patel, A., Baameur, F., Gurevich, V. V., Craft, C. M., Kefalov, V. J., Roberts, R. Development of an MRI biomarker sensitive to tetrameric visual arrestin 1 and its reduction via light‐evoked translocation in vivo. FASEB J . 29, 554‐564 (2015). www.fasebj.org